Implementasi E-Monitoring Aktivitas Siswa Pada SMKN 5 dan SMKS 2 Medan Putri Berbasis Web - Ramadhani, Fanny; Al-Khowarizmi, Al-Khowarizmi; Hutagalung, Fatma Sari (University of Muhammadiyah Sumatera Utara, 2021)
SMK Negeri 5 Medan is one of the vocational high schools in the city of Medan. One of the visions and missions of this school is to increase discipline in complying with existing regulations. One of the things that must be disciplined is attendance, timely collection of assignments and payment of tuition fees that must be on time. But in reality there are still some students who do not attend school because the student withdraws so that parents feel worried about the condition of their children at school, whether they actually go to school or not and parents also cannot know the progress of how many grades their children have earned in general directly because of busy work, there are even students who cannot maintain the mandate to pay tuition fees that have been deposited by their parents. Therefore, a system is needed to monitor student activities at school. Monitoring activities are the main activities in the world of education. However, these activities cannot be carried out optimally. Parents still find it difficult to monitor their children's learning activities at school. Notification of student achievement (grades) is only made at the time of receipt of the final report. Therefore we need a system that facilitates the process of monitoring and assessing students, both for teachers and parents to overcome these problems. The purpose of this research is to develop a student monitoring system (E-Monitoring). The method used to develop this system is data collection, hardware and software analysis, system design and analysis as well as system implementation and testing. The result of this study is a system that can assist teachers in managing grades, recap student errors, and facilitate parents to monitor and obtain information about their children's learning activities clearly and in real time.